1977
DOI: 10.1161/01.res.41.3.350
|View full text |Cite
|
Sign up to set email alerts
|

Total and regional cerebral blood flow during hypotension, hypertension, and hypocapnia. Effect of sympathetic denervation in dogs.

Abstract: CEREBRAL blood vessels are innervated by adrenergic nerve fibers from the cervical sympathetic chain.1 -2 The main source of this sympathetic innervation is the superior cervical ganglion, 3 with a small contribution in dogs from the stellate ganglion. 4 Although cerebral vessels are densely innervated, the significance of these sympathetic nerves in regulation of cerebral blood flow (CBF) is controversial.Several previous studies have evaluated the functional significance of sympathetic nerves by examining re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
43
1
3

Year Published

1977
1977
2011
2011

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(50 citation statements)
references
References 31 publications
3
43
1
3
Order By: Relevance
“…In 1977, a group studying the CBF response to hypotension in dogs unexpectedly observed a selective reduction of blood flow in their single white matter region of interest located in the centrum semiovale. 47 Five years later, a similar study revealed selective reduction of blood flow in 3 of 5 white matter regions assessed: a periventricular region, a deep white matter region, and a visual radiation region. 48 There is one study 26 that provides evidence of a steal phenomenon in the white matter of normal human subjects.…”
Section: Discussionmentioning
confidence: 85%
“…In 1977, a group studying the CBF response to hypotension in dogs unexpectedly observed a selective reduction of blood flow in their single white matter region of interest located in the centrum semiovale. 47 Five years later, a similar study revealed selective reduction of blood flow in 3 of 5 white matter regions assessed: a periventricular region, a deep white matter region, and a visual radiation region. 48 There is one study 26 that provides evidence of a steal phenomenon in the white matter of normal human subjects.…”
Section: Discussionmentioning
confidence: 85%
“…In previous studies we have demonstrated regional differences in the response to decreases in cerebral perfusion pressure in normotensive dogs 10 and rabbits. 11 We found that hypotension redistributes CBF, so that blood flow to brainstem is maintained better than flow to cerebrum or cerebellum.…”
mentioning
confidence: 83%
“…At present, the myogenic vasomotor mechanism is used primarily to explain the presence of autoregulation of CBF, which aims to protect the brain from high volume and pressure (Faraci et al, 1989;Harper et al, 1984;Mellander, 1989;Mueller et al, 1977). Much less is known regarding the role of flowdependent regulation of CBF, although in vivo during changes in pressure, flow changes, as well.…”
Section: Flow-induced Constriction Of Isolated Cerebral Arteries and mentioning
confidence: 99%